Clinical Evaluation of Safety and Efficacy of a 670-nm Picosecond Laser for Treatment of Benign Pigmented Lesions in Asians. Issue 5 (23rd May 2021) - Evangelista, Kristy E.R.; Manuskiatti, Woraphong; Wanitphakdeedecha, Rungsima; Techapichetvanich, Thanya
Abstract : BACKGROUND: Picosecond lasers are increasingly being investigated in treating pigmentation disorders because they may provide better treatment efficacy and comfort compared with nanosecond lasers. OBJECTIVE: This study aims to evaluate the efficacy and side effect of a novel 670-nm picosecond laser in the removal of benign pigmented lesions (BPLs) in individuals with Fitzpatrick skin types (FST) III and IV. MATERIALS AND METHODS: Fifteen subjects with solar lentigines and 7 subjects with ABNOMs received a single treatment with a 670-nm picosecond laser. Blinded physicians assessed the pigment clearance using a 5-category grading system scale. All subjects were evaluated at 1 month, 3 month, and 6 month after a single treatment. Adverse events were recorded at every follow-up visit. RESULTS: All subjects with lentigines had complete clearance (95%–100%) of lesions during 3-month follow-up after a single treatment session of 670-nm picosecond laser, whereas 75% of the subjects with ABNOMs noted fair lightning (25%–49%) of lesions. Mild hypopigmentation and hyperpigmentation were observed in 9% and 14% of the subjects, respectively, which resolved within 3 months after the treatment. CONCLUSION: The novel 670-nm picosecond laser is a safe and effective treatment for BPLs in subjects with FST III and IV with low rates of transient adverse effects.